Collaborative product development implementation between Malaysian auto suppliers and their customer - Mohd Razali, Muhamad; Norizah , Mohamad; H., Hussain; A.R., Songi; S.N., Othman (2004)
Whilst the evidence indicated that supplier involvement in product development resulted in reduced development cost, improves product quality, reduces lead time and enhances flexibility, the mechanism for adapting and managing it to fit an.other culture and organisation is a challenging endeavour. In the Malaysian automotive industries, this collaborative effort had been mostly motivated by the government policies and initiated by the anchor firms. The work reported in the paper describes features of this collaboration carried out by Proton, the pioneer automotive manufacturing company in Malaysia. The objective of this paper is to examine the factors for successful collaborative product development endeavours. The study identifies how collaborative product development is presently being organized and managed in the automotive industry in Malaysia. The product development process is traced to the three aspects involved in collaborative product development; the buyer, the supplier and the process that involves both parties. The findings from this study suggest that from the buyer perspectives, selection of suppliers determines the success of this effort. For the supplier, it is important for them to have technical and design expertise. Factors that involve both the suppliers and buyers include early supplier involvement and buyer-supplier relationships.